BIOMAS BRASILEIROS EM LIVROS DIDÁTICOS DE BIOLOGIA: APRECIAÇÃO DAS COLEÇÕES APROVADAS NO PNLD 2018 - Lopes, Michel Pimentel (2018)
The term “biome” is commonly used in classrooms and non-formal spaces. According to the Brazilian Institute of Geography and Statistics (IBGE), a biome can be defined as a community of living organisms (plants and animals) constituted by the grouping of contiguous vegetation types identifiable on a regional scale with similar geo-climatic conditions and a shared history, which results in a unique biological diversity. Thus, this qualitative study aims to analyse how the topic “biomes” is presented and contextualized in biology textbooks. For this purpose, nine collections of biology textbooks already approved by the Brazilian National Textbook Program (PNLD) / 2018 were analysed with regard to the following aspects: the concept of “biome”, the classification of Brazilian biomes and the information provided about Brazilian biomes, as found in the collections analysed. The results show that all the collections analysed present the topic “biomes” as well as its definition. Similarly, they all approach the Brazilian biomes, although there is no uniformity in the classifications adopted by the authors. In addition, two of the collections discuss the topic investigated by presenting the Brazilian morphoclimatic zones, but they do not take into account the biomes themselves. In general, they all present the characteristics of a biome in terms of biodiversity, however, they emphasize the taxonomic and ecosystemic levels. In conclusion, they all present some information about the human impact on biomes, but only two collections focus on their conservation.